PENGARUH PRICE DISCOUNT DAN IN STORE DISPLAY TERHADAP IMPULSE BUYING PADA MINISO STORE DUTA MALL BANJARMASIN - Syahreza Akbar; Rizky Muslim Hidayat; Fitriyadi; Irwansyah (Business Administration, FISIP ULM, 2024)
This study aims to determine the impact of in-store displays and price reductions on impulsive buys at Miniso Store Duta Mall Banjarmasin. The quantitative technique of this study makes use of the explanatory research type and survey research design. The sample for this study consisted of 100 respondents selected using accidental sampling. Questionnaires are used for data collection, and SPSS (Statistical Product and Service Solutions) is used for data analysis. The exploration results demonstrate that Value Rebate fundamentally affects Motivation Purchasing, In Store Show essentially affects Drive Purchasing, Value Markdown and In Store Show have a tremendous impact all the while Without really thinking Purchasing at the Miniso Store Duta Shopping center Banjarmasin.